Analisis Kesalahan Siswa Kelas VIII SMP Batik Surakarta dalam Memecahkan Soal Matematika Model PISA Konten Space and Shape. - Cahyanto, Muhamat Nur; , Sri Rejeki, M.Pd., M.Sc (2017)
This study aimed to describe, calculate the percentage and to find out the factor causing of students error in solving math problem based PISA the space and shape content. This study is a qualitative descriptive. The subject of study were VIII B grade student of SMP Batik Surakarta totaling 33 student. Data collection was conducted using observation, tests, interviews and documentation. The data validation was done by triangulation method by comparing the data of the observation, tests, interviews and documentation. Technique of analyzing data used included data reduction, data presentation and conclusion drawing. An analysis framework was developed based on process correctly according to step Polya and Newman's error categories. The result of study were obtained types of errors and percentage for each type of error, were comprehension errors 37,07 %, transformation error 19,83 %, processing error 15,52 % and encoding error 27,59 %. The results showed that comprehension error and encoding error is the more dominant errors than the other error. In general, the factors solving on real context and manipulating it into algebraic form. The most influentional factor is the students are not accustomed to using the troubleshooting process correctly according to step Polya.